Pengelolaan Lingkungan Kelas Sebagai Sarana Bermain Sambil Belajar Bagi Anak TK - Beatriks Novianti Bunga; Maria L. B. Koten; Angelikus Nama Koten (Journal of Health and Behavioral Science, 2019)
Competent teacher can improve their abilities in managing classroom according to their students’ needs. Classroom management in early childhood education and development (ECED) post really depends on the teacher. This article aims to understand classroom management as tools of playing and studying for children in kindergarten. This study used qualitative descriptibe approach and triangulation was used to ensure the data quality. Between for class observed, class B1 was identified as the most ideal. Good ventilation and lighting, neat placement of equipments and class tools, not blocking air circulation, according to area and not blocking children play zone, also neat class decoration and clean and comfort class describe this overall class management quality.